Antihypertensive treatment decreases arterial stiffness at night but not during the day. Results from the Hypertension in the Very Elderly Trial. (4th March 2017) - Bulpitt, Christopher J.; Webb, Richard; Beckett, Nigel; Peters, Ruth; Cheek, Elizabeth; Anderson, Craig; Antikainen, Riitta; Staessen, Jan A.; Rajkumar, Chakravarthi
Abstract: The main Hypertension in the Very Elderly Trial (HYVET) demonstrated a very marked reduction in cardiovascular events by treating hypertensive participants 80 years or older with a low dose, sustained release prescription of indapamide (indapamide SR, 1.5 mg) to which was added a low dose of an angiotensin converting enzyme inhibitor in two-thirds of cases (perindopril 2–4 mg). This report from the ambulatory blood pressure sub-study investigates whether changes in arterial stiffness and ambulatory blood pressure (BP) could both explain the benefits observed in the main trial. A total of 139 participants were randomized to placebo [67] and to active treatment [72] and had both day and night observations of BP and arterial stiffness as determined from the Q wave Korotkoff diastolic (QKD) interval. The QKD interval was 5.6 ms longer ( p = 0.017) in the actively treated group at night than in the placebo group. This was not true for the more numerous daytime readings so that 24-h results were similar in the two groups. The QKD interval remained longer at night in the actively treated group even when adjusted for systolic pressure, heart rate and height. The reduced arterial stiffness at night may partly explain the marked benefits observed in the main trial.